2003
DOI: 10.1142/s0129183103004528
|View full text |Cite
|
Sign up to set email alerts
|

GENERALIZED (m, k)-ZipfLAW FOR FRACTIONAL BROWNIAN MOTION-LIKE TIME SERIES WITH OR WITHOUT EFFECT OF AN ADDITIONAL LINEAR TREND

Abstract: We have translated fractional Brownian motion (FBM) signals into a text based on two "letters", as if the signal fluctuations correspond to a constant stepsize random walk. We have applied the Zipf method to extract the ζ ′ exponent relating the word frequency and its rank on a loglog plot. We have studied the variation of the Zipf exponent(s) giving the relationship between the frequency of occurrence of words of length m < 8 made of such two letters: ζ ′ is varying as a power law in terms of m. We have also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Thus, it is concluded that the sample of the daily returns has significant autocorrelation and partial autocorrelation at lag 4. It can be deduced that such a finding indicates that the stock price can be predicted on such a time span (Ausloos and Bronlet, 2003;Bronlet and Ausloos, 2003).…”
Section: Spot Market Volatilitymentioning
confidence: 82%
“…Thus, it is concluded that the sample of the daily returns has significant autocorrelation and partial autocorrelation at lag 4. It can be deduced that such a finding indicates that the stock price can be predicted on such a time span (Ausloos and Bronlet, 2003;Bronlet and Ausloos, 2003).…”
Section: Spot Market Volatilitymentioning
confidence: 82%
“…In Appendix D, we provide Figures A6-A10, which show the evolution of Yang-Zhang and intrinsic entropy-based estimates for Dow 30, Russel 2000, NASDAQ Composite, Nikkei 225, and Hang Seng stock market indices, respectively, over a time window of 260 days, going backwards from 31 January 2021. From this different perspective of market volatility, we note that the intrinsic entropy-based volatility estimates may have a more useful role in emphasizing the fractured nature of the market [28,29]. Robert A.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this observation of "relatively strong price movements" has something to do with the interest that the investors show in those securities, something which may be due to the fundamentals of those securities. The intrinsic value of these securities appears to From this different perspective of market volatility, we note that the intrinsic entropybased volatility estimates may have a more useful role in emphasizing the fractured nature of the market [28,29]. Robert A.…”
Section: Discussionmentioning
confidence: 99%
“…Another sort of data analysis technique can be adapted to portfolio management (Ausloos & Bronlet, 2006), leading to forecasting and prediction, with some ‘risk’: it is known as the Zipf technique, originating in work exploring the statistical nature of languages (Zipf, 1949); see Appendix 3. The Zipf method previously developed as an investment strategy (on usual financial indices) (Ausloos & Bronlet, 2003; Bronlet & Ausloos, 2003) can be adapted to portfolio management.…”
Section: Micro-econophysicsmentioning
confidence: 99%